Pengelolaan Konten Media Sosial Sebagai Sarana Pemasaran Usaha Kecil Warga Kampung Anyar, Kabupaten Bogor - Hamzah, Radja Erland; Sungkono, Nono; Santoso, Prasetya Yoga (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Community service activities aim to empower the community through social media content management training for marketing tools. Providing information to the public how big the role of social media is as a tool in marketing. This training activity was carried out in Tegal Village, Kemang District, Bogor Regency. Most of the residents who attended owned small businesses so this training was effective because it targeted people who wanted to take advantage of social media to increase online sales. The method used in this activity is in the form of lectures and training in using social media such as Facebook and Instagram. Residents are also taught how to use the Whatsapp Business application for free. The results of the activity provide sufficient benefits to have an impact on the use of social media marketing which is a medium that has low costs and is very effective in disseminating information online in marketing small businesses belonging to the people of Kampung Anyar, Desa Tegal, Bogor.